Cerdas Digital dengan Artificial Intelligence: Solusi Teknologi untuk Pelayanan dan Keamanan Publik - Tristanti, Novi; Fanani, Galih Pramuja Inngam; Romadloni, Nova Tri; Efendi, Burhan; Setiani, Hani (Apik Cahaya Ilmu, 2025)
Artificial intelligence (AI)-based digital technology presents both opportunities and challenges for village security officers, particularly Village Supervisory Non-Commissioned Officers (Bhabinkamtibmas), in addressing the spread of hoaxes and meeting the demands for fast and efficient public services. The low level of digital literacy and practical skills in utilizing AI at the village level prompted the implementation of a community service program titled “Digital Intelligence with Artificial Intelligence: Technological Solutions for Public Service and Security.” This program aimed to enhance Bhabinkamtibmas’s understanding and ability to apply AI in public service and village security. The method used was a combination of theoretical and practical training for 30 Bhabinkamtibmas participants, covering three main topics: chatbot utilization for public services, face recognition for security support, and AI-based hoax content detection. Effectiveness was evaluated through pretest and posttest assessments. The results showed an average improvement of 40%, with posttest scores reaching 85% for chatbot usage, 80% for face recognition, and 75% for hoax detection. These findings demonstrate that practice-based training effectively improves Bhabinkamtibmas’s digital literacy and technical skills. In conclusion, this program successfully equips Bhabinkamtibmas as digital literacy agents capable of leveraging AI to strengthen public services and village security, contributing to the development of an adaptive Smart Policing ecosystem in the digital era.